The effect of long-term wastewater cross-connection on the biofilm of a simulated water distribution system. Issue 2 (1st March 2003) - Gibbs, Shawn G; Meckes, Mark C; Scarpino, Pasquale V
Abstract : The drinking water distribution system simulator (DSS) from the U.S. EPA was used to assess the effect of long-term wastewater cross-connection on the biofilm of a simulated water distribution system. Initial experimentation determined that at 0.3% wastewater to system volume per day for 90 d injected 0.1% every 8 h into the DSS; study organisms were consistently present in the discharge water sample with only slight aesthetic problems (increased turbidity). During the cross-connection, incoming tap water and wastewater, and system discharge water were monitored to ensure that the source of study organisms was only the wastewater cross-connection and that study organisms were present in the water column of the DSS. Following elimination of the cross-connection, samples showed that study organisms were removed from the water column within 24 h, which was the hydraulic retention time of the system. Increased numbers of heterotrophic organisms were detected in the system discharge following cross-connection. Increased heterotrophs were recovered for the system biofilm, and study organisms, except culturable heterotrophs, were not recovered beyond 24 h. Results indicate that the existing biofilm grew during the cross-connection, and may have inhibited growth of specific study organisms introduced via the cross-connection. Key words : biofilm, wastewater, drinking water, microorganisms, cross-connection.